2015
DOI: 10.3906/biy-1502-32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Western-style diet high in cholesterol and saturated faton the rabbit exocrine pancreas

Abstract: Despite the well-known cardiovascular effects of an atherogenic diet, there are no data relating to its effect on the exocrine pancreas. Therefore, the aim of this study was to investigate the consequences of this eating pattern on the exocrine pancreas. Twelve New Zealand rabbits were randomised to one of two dietary groups, control group (C) and hypercholesterolemic (HCHOL), that were fed for 50 days with a standard chow or a diet containing 95.7% standard chow, 3% lard, and 1.3% cholesterol, respectively. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Moreover, some studies indicate that fatty acid composition in the diet can affect α amylase activity. Additionally, experiments performed on diabetic rats have shown that unsaturated fatty acids, such as oleic acid, linoleic acid and palmitoleic acid, and saturated fatty acids, such as stearic acid and palmitic acid, reduce amylase activity [36]. On the other hand, some research did not show any effect of dietary lipid content on amylase activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies indicate that fatty acid composition in the diet can affect α amylase activity. Additionally, experiments performed on diabetic rats have shown that unsaturated fatty acids, such as oleic acid, linoleic acid and palmitoleic acid, and saturated fatty acids, such as stearic acid and palmitic acid, reduce amylase activity [36]. On the other hand, some research did not show any effect of dietary lipid content on amylase activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…In control group, the LDL level was increased. This could be affected by saturated fatty acids (SFA) intake [32,33]. High SFA diet could reduce the catabolism of LDL apoB-100 fractional, hence it will increase plasma LDL levels, however this effect is very dependent on types of saturated fatty acids consumed [34].…”
Section: Discussionmentioning
confidence: 99%